SOCIAL RESPONSIBILITY AS AN INTEGRAL INSTRUMENT OF STATE POLICY OF IMPLEMENTATION OF SOCIAL DIALOGUE IN THE CONDITIONS OF SOCIALISATION OF TRADE - MAZIARKO, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article summarizes the manifestations of social responsibility of economic entities and employees in trade as a tool of state policy for the implementation of social dialogue in the context of socialization. Social dialogue in trade is a means of state policy of forming a favorable systemically and structurally balanced environment in the social and labor sphere of the industry, focused on improving the quality of working life, implementation of socio-economic development programs, providing preconditions for natural sustainable socio-economic development. interests of all subjects and participants of social dialogue. Obviously, social dialogue is a prerequisite for creating a new conceptual model of social and labor relations, based on the development, adoption and implementation of partnership socially-oriented management decisions. Also, social dialogue allows by achieving a balance of interests, opinions and positions to find mutually acceptable solutions for the parties. Social responsibility is defined as independent, proactive, systematic activity of business entities to form relationships with society, government, the public, partners in order to coordinate and / or meet the social, economic, financial, ethical interests of all groups of interested users on mutually beneficial terms to achieve both economic and social results. The necessity of socialization in trade, the influence of psychological factors and the satisfaction of employees' needs on the formation of the institutional system of social responsibility are substantiated. The concept of social dialogue and social responsibility in trade are determined, and that the result of social dialogue of its subjects, which are the state, trade unions and employers, is a balanced achievement of goals of staff, management, the state in particular on social responsibility. The relationship between the concepts of social dialogue and social responsibility in trade is specified. It is proposed to strengthen the work motivation and social protection of employees through collective bargaining regulation of the use of such an institutional tool as the "social package". An effective mechanism for the implementation of social dialogue in the form of collective bargaining has been developed.
Keywords: social responsibility; social dialogue; socialization; state regulation; public policy; trade